Behavioral weight loss for the management of menopausal hot flashes: a pilot study. Issue 1 (January 2015) - Thurston, Rebecca C.; Ewing, Linda J.; Low, Carissa A.; Christie, Aimee J.; Levine, Michele D.
Abstract: Objective: Although adiposity has been considered to be protective against hot flashes, newer data suggest positive relationships between hot flashes and adiposity. No studies have been specifically designed to test whether weight loss reduces hot flashes. This pilot study aimed to evaluate the feasibility, acceptability, and initial efficacy of behavioral weight loss in reducing hot flashes. Methods: Forty overweight or obese women with hot flashes (≥4 hot flashes/d) were randomized to either behavioral weight loss intervention or wait-list control. Hot flashes were assessed before and after intervention via physiologic monitoring, diary, and questionnaire. Comparisons of changes in hot flashes and anthropometrics between conditions were performed via Wilcoxon tests. Results: Study retention (83%) and intervention satisfaction (93.8%) were high. Most women (74.1%) reported that hot flash reduction was a major motivator for losing weight. Women randomized to the weight loss intervention lost more weight (−8.86 kg) than did women randomized to control (+0.23 kg; P < 0.0001). Women randomized to weight loss also showed greater reductions in questionnaire-reported hot flashes (2-wk hot flashes, −63.0) than did women in the control group (−28.0; P = 0.03)—a difference not demonstrated in other hot flash measures. Reductions in weight and hot flashes were significantly correlated (eg, r = 0.47, P = 0.006). Conclusions: This pilot study shows a behavioral weight loss program that is feasible, acceptable, and effective in producing weight loss among overweight or obese women with hot flashes. Findings indicate the importance of a larger study designed to test behavioral weight loss for hot flash reduction. Hot flash management could motivate women to engage in this health-promoting behavior.